Implementation Of Mudharabah Financing On Baitul Maal According Majlis Ulama Indonesia - Meta Riskia (Journal of Nusantara Economy, 2022)
This study aims to answer a problem regarding how the implementation of mudharabah financing in Baitul Mal Hidayatullah, Bengkulu City, and how to review the DSN MUI fatwa No.07/DSN-MUI/IV/2000 concerning mudharabah financing for the implementation of mudharabah financing in Baitul Mal Hidayatullah, Bengkulu city. The method used in this research is field research, namely research conducted directly in the field to obtain the necessary data and research whose object is the symptoms or events that occur in a community group. Based on the study results, the losses resulting from the business carried out by the mudharib are entirely borne by the BMH and claim the mudharib as a poor person, so there is no need to return the capital that the mudharib has taken. Moreover, the mudharib is not charged with a fine by the BMH but is given a period (rappel) until the mudharib can agree to return the funds. So, the baitul mal hidayatullah itself has not optimally implemented DSN Fatwa No. 07/DSN-MUI/IV/2000 regarding mudharabah financing. Although the BMH bears all losses experienced by the mudharib, the BMH party does not provide 100% capital to the mudharib. penelitian ini bertujuan untuk menjawab suatu permasalahan mengenai bagaimana pelaksanaan pembiayaan mudharabah di baitul mal hidayatullah kota bengkulu serta bagaimana tinjauan fatwa DSN MUI No.07/DSN-MUI/IV/2000 tentang pembiayaan mudharabah terhadap pelaksanaan pembiayaan mudharabah di baitul mal hidayatullah kota Bengkulu. Metode yang digunakan dalam penelitian ini ialah field research yaitu penelitian yang dilakukan secara langsung di lapangan untuk memperoleh data yang diperlukan dan penelitian yang obyeknya mengenai gejala-gejala atau peristiwa yang terjadi pada suatu kelompok masyarakat. Berdasarkan hasil penelitian bahwasanya kerugian akibat dari usaha yang dilakukan oleh mudharib dibebankan  sepenuhnya oleh pihak BMH dan mengklaim si mudharib ini sebagai fakir miskin sehingga tidak perlu mengembalikan modal yang telah mudharib ambil. Dan pihak mudharib sendiri tidak dibebankan denda oleh pihak BMH akan tetapi diberikan jangka waktu (rapple) sampai pihak mudharib ini bisa menyetujui pengmbalian dana tersebut ataukah tidak. Sehingga bisa kita dikatakan, baitul mal hidayatullah ini sendiri belum secara optimal dalam melaksanakan Fatwa DSN No. 07/DSN-MUI/IV/2000 tentang pembiayaan mudharabah. Meskipun, pihak BMH menanggung segala bentuk kerugian yang dialami oleh mudharib akan tetapi pihak dari BMH tidak memberikan modal 100% kepada pihak mudharib.